GAMBARAN ASUPAN MAKAN REMAJA HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS MONDOKAN KABUPATEN SRAGEN - Hanin Imtinan Alwina; Martha Irene Kartasurya; Siti Fatimah Pradigdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Adolescent pregnancy is at risk for complications, it increases mordibity and mortality in both mother and fetus. Mondokan region is one of the regions that having the highest number of pregnant adolescent in Sragen Regency. The purposes of this research is to describe food intake among pregnant adolescent 3rd trimester in Mondokan health center working area, in Sragen. This research a qualitative study. Thirty one pregnant adolescents were chosen as the subjects, purposively. Data were collected by interviews using structured questionnaires and the nutitrion intake was measured by were 2x24 hours recall. The results showed that the average age of respondents was 17,90 ± 1,04 years. Most of the subjects were only graduated from junior high school (71%) and 77.4% of the families had income lower than the district minimum wage. There was no respondent who had history of infectious diseases. The average of energy adequacy level was 51.5%, protein adequacy level 59.9%, vitamin C adequacy level 87.7%, vitamin B12 adequacy level 47.5%, folic acid adequacy level 31.9%, and iron adequacy level 45.6%. It was concluded that the average intake of nutrients were much lower than the adequacy level. This causes adolescent pregnancy give low birth weight.